Distinct Cause of Death Profiles of Hospitalized Non-alcoholic Fatty Liver Disease: A 10 Years' Cross-Sectional Multicenter Study in China - Lin, Yansong; Gong, Xiaorong; Li, Xin; Shao, Congxiang; Wu, Tingfeng; Li, Minrui; Li, Fuxi; Ma, Qianqian; Ye, Junzhao; Zhong, Bihui (Frontiers in Medicine, 2021)
Background: The clinical burden and natural history of non-alcoholic fatty liver disease (NAFLD) vary globally. We aimed to investigate NAFLD-related mortality profiles in hospitalized patients in southern China. Methods: A multicenter retrospective investigation with a 10-year study period (2009–2018) analyzed 10,071 deaths during hospitalization (NAFLD: 2,015; other liver diseases: 1,140; without liver diseases: 6,916) was performed using a multiple cause of death analysis. Medical histories and biochemistry and imaging findings were extracted from the electronic medical record system. The underlying causes of death were classified by 10th Revision of the International Classification of Diseases (ICD-10) codes. Results: The distribution of death causes in patients with NAFLD has stabilized over time, with cardio- and cerebral vascular disease (CVD) ranked first (35.6%), followed by extrahepatic malignancies (22.6%), infection (11.0%), kidney disease (7.5%), liver-related diseases (5.2%), respiratory diseases (3.9%), digestive diseases (3.5%), endocrine diseases (3.5%), and other diseases (7.2%). NAFLD patients had more deaths attributable to CVD, extrahepatic malignancies, liver-related diseases (all P < 0.001) and multiorgan failure than the deceased controls. The severity of steatosis was independently associated with these relationships (liver-related diseases: OR = 1.37, 95% CI: 1.20–1.59, cardio- and cerebrovascular diseases: OR = 1.23, 95% CI: 1.19–1.31, infectious diseases: OR = 1.14, 95% CI: 1.04–1.26, and renal diseases: OR = 1.21, 95% CI: 1.02–1.47, all P < 0.05) after adjustment for sex, body mass index (BMI), fasting blood glucose, low-density lipoprotein cholesterol, uric acid, metabolic syndromes and fibrosis index based on the 4 factors. Conclusion : NAFLD patients had higher proportions of death due to underlying CVD and liver-related diseases than the general population in China; these proportions positively correlated with steatosis degree.